(untitled) (Mongolian Journal of Humanities and Social Sciences, 2024)
This paper will compared the words and concepts related to religion in Mongolian and Korean languages, which have branched from the ancestral Altaic language, in the sources of Mongŏyuhae(蒙語類解) and (Panŏnčibsog) (方言集釋). One of the sources known as The Three Books for the Study of Mongolian (蒙語類解) and the similar 5 language dictionary (Panŏnčibsog) (方言集釋) were used as source materials. It is important to bring these sources belonging to the XVII-XVIII centuries into the research circulation, to compare the words and concepts related to religion in Mongolian and Korean languages, which have branched out from the ancestral Altaic language, in the sources of Chosŏn Dynasty (Korean Empire in 1392-1897). Mongŏ-yuhae (蒙語類解) and Panŏn-čibsog (方言集釋) сурвалж дахь шашны холбоотой үг хэллэгийн харьцуулсан судалгаа Хураангуй: Тухайн үндэстний соёл, сэтгэлгээний гол илэрхийлэл, үгийн утгын баялаг уурхай бол толь бичиг байдаг. Тийм ч учраас эрдэмтэд “Толь бичиг нь үгсийн цомог, тайлбар төдий зүйл бус, үндэстний соёл сэтгэлгээний нэг хэсэг юм. Дорно дахины толь бичгийн уламжлалыг хадгалан бичсэн Солонгос улсын Чусон үеийн монгол хэлний зүйл хуваасан 3 ба 5 хэлний толь бичигт буй шашны холбоотой үг хэллэгийн гарал хийгээд Монгол, Солонгос хэлэнд илэрхийлж буй утга, стэгэлгээний онцлогийг харьцуулан авч үзлээ. Түлхүүр үг: концепц, шашны холбоотой үг хэллэг, Mongŏ-yuhae 3 хэлний толь, Panŏn-čibsog 5 хэлний толь